2008
DOI: 10.1002/cphc.200800300
|View full text |Cite
|
Sign up to set email alerts
|

Physical Vapor Deposition of [EMIM][Tf2N]: A New Approach to the Modification of Surface Properties with Ultrathin Ionic Liquid Films

Abstract: Ultrathin films of the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMIM][Tf(2)N], are prepared on a glass substrate by means of an in situ thermal-evaporation/condensation process under ultrahigh-vacuum conditions. By using X-ray photoelectron spectroscopy (XPS), it is demonstrated that the first layer of the IL film grows two dimensionally, followed by the three-dimensional growth of successive layers. The first molecular layer consists of a bilayer, with the [EMIM](+) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
200
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(217 citation statements)
references
References 64 publications
15
200
1
1
Order By: Relevance
“…[ 111 ] These results on the Au(111) surface are quite different to the results found for [C 2 C 1 Im][Tf 2 N] on a glass substrate in previous work. [ 49 ] It could be demonstrated in this latter case that the fi rst layer of the IL fi lm wets the glass surface in a two dimensionally fashion. In contrast to the gold substrate, the fi rst layer consists of a bilayer, with the [C 2 C 1 Im] + cations in direct contact to the glass surface and the [Tf 2 N] − anions at the vacuum side.…”
Section: Progress Reportmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 111 ] These results on the Au(111) surface are quite different to the results found for [C 2 C 1 Im][Tf 2 N] on a glass substrate in previous work. [ 49 ] It could be demonstrated in this latter case that the fi rst layer of the IL fi lm wets the glass surface in a two dimensionally fashion. In contrast to the gold substrate, the fi rst layer consists of a bilayer, with the [C 2 C 1 Im] + cations in direct contact to the glass surface and the [Tf 2 N] − anions at the vacuum side.…”
Section: Progress Reportmentioning
confidence: 98%
“…Therefore, recent attempts to prepare IL fi lms in-situ and under UHV conditions represent an important progress in IL surface science. [ 49 ] In principle, thick fi lms can also be prepared in-situ by dipping a sample surface into an IL reservoir inside the UHV chamber. However, the best-controlled method to prepare thin IL fi lms is by physical vapor deposition (PVD).…”
Section: Preparation and Spectroscopy Of Ionic Liquid Films And Intermentioning
confidence: 99%
See 1 more Smart Citation
“…for the controlled deposition of ultrathin IL films. 12,13 It may, however, also limit technical operation with ionic liquids in open systems at high temperatures. Recently, it has been shown that special TG experiments allow discriminating between thermal decomposition and evaporation by applying a combination of non-isothermal ambient pressure measurements with an overflow of inert gas with isothermal experiments conducted under high vacuum using a magnetic suspension balance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ILqds have been applied to the architecture of smart surfaces with their counteranion-responsiveness to exhibit their hydrophilicity and hydrophobicity by simply exchanging counteranions [13][14][15] . Thus, utilization of this switching behavior opens a new way to control the properties of the material surface [16][17][18][19][20] .…”
mentioning
confidence: 99%